2023
DOI: 10.3390/ijerph20031682
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Inflammation and Role of Anti-Inflammatory Diet in Childhood Obesity

Abstract: At present, pediatric obesity is a significant public health concern. We have seen a surge of disorders that are obesity-related, e.g., insulin resistance (IR), type 2 diabetes mellitus (T2DM), high blood pressure, heart disease, stroke, cancer, non-alcoholic fatty liver disease (NAFLD), autoimmune disorders and many more. The mechanisms linking these diseases to excess body weight are related to low-grade inflammation (LGI). Although there is a limited number of studies assessing this immune process in childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
0
6
0
1
Order By: Relevance
“…Diet is considered one of the major contributors to obesity. Recent studies have shown that the WD pattern, rich in SFAs and trans fats but low in omega-3 PUFAs, contributes to both insulin resistance and the increased secretion of inflammatory markers [41,42]. Additionally, children and adolescents adopting a "sweet dietary pattern", rich in cakes, pastries, sweets, and soft drinks, are at higher risk for abdominal obesity, elevated blood pressure, and MetS [43], and sweets' consumption is associated with unfavorable cardiometabolic health outcomes, including higher levels of triacylglycerol, Very-Low-Density Lipoprotein (VLDL) cholesterol, and higher levels on the insulin resistance index (HOMA-IR) [44,45].…”
Section: Diet-related Diseases Obesity and Metabolic Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Diet is considered one of the major contributors to obesity. Recent studies have shown that the WD pattern, rich in SFAs and trans fats but low in omega-3 PUFAs, contributes to both insulin resistance and the increased secretion of inflammatory markers [41,42]. Additionally, children and adolescents adopting a "sweet dietary pattern", rich in cakes, pastries, sweets, and soft drinks, are at higher risk for abdominal obesity, elevated blood pressure, and MetS [43], and sweets' consumption is associated with unfavorable cardiometabolic health outcomes, including higher levels of triacylglycerol, Very-Low-Density Lipoprotein (VLDL) cholesterol, and higher levels on the insulin resistance index (HOMA-IR) [44,45].…”
Section: Diet-related Diseases Obesity and Metabolic Syndromementioning
confidence: 99%
“…("Inflammation"[Mesh] OR "Diet, Western"[Mesh] OR "Food, Processed"[Mesh] OR "Ultra-processed food"[Title/Abstract] OR "Diet Therapy"[Mesh] OR "special diet" [tiab]) AND ("allerg*" [tiab] OR "food allerg*" [tiab] OR "Food Hypersensitivity" ("Inflammation"[Mesh] OR "Diet, Western"[Mesh] OR "Food, Processed"[Mesh] OR "Ultra-processed food"[Title/Abstract] OR "Diet Therapy"[Mesh] OR "Diet, Gluten-Free"[Mesh] OR "special diet" [tiab]) AND ("Celiac Disease"[Mesh] OR "coeliac disease" [tiab]) AND ( :2023) AND (allchild [Filter]). Number of documents = 958 8.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended to add spices to dishes: turmeric, ginger, saffron, cloves, cinnamon, and nutmeg. Recommended liquids are water, green and black tea [9].…”
Section: Characteristics Of the Anti-inflammatory Dietmentioning
confidence: 99%
“…Do potraw rekomendowany jest dodatek przypraw: kurkumy, imbiru, szafranu, goździków, cynamonu, gałki muszkatołowej. Zalecane płyny to woda, zielona oraz czarna herbata [9]. Na szczycie piramidy diety przeciwzapalnej opublikowanej przez Rondanelli i wsp.…”
Section: Wyniki 1 Charakterystyka Diety Przeciwzapalnejunclassified